Characterization of Imprinted Polymer of Diazepam With Methacrylic Acid and Hydroxyethyl Methacrylate Monomer in Chloroform for Selective Adsorption of Diazepam - Michelle Ferdinand; Rimadani Pratiwi; Aliya Nur Hasanah (Indonesian Journal of Pharmaceutical Science and Technology, 2020)
Diazepam is a benzodiazepine class usage is regulated nationally or globally. These drugs can be used to regulate sleep patterns or sedative-hypnotic drugs because it has a calming effect. Monitoring the abuse of diazepam requires a sensitive analysis methods that required the preparation of selective methods. One of the methods that are currently developing is Moleculary Imprinted Polymer-Solid Phase Extraction (MI-SPE). In this research, step being performed include determination of the association constant, synthesis sorbent of Imprinted Polymer (IP) diazepam by bulkpolymerization method with diazepam as a template, chloroform as porogen, two kind of monomer methacrylic acid (MAA) and hydroxyethyl methacrylate (HEMA) as functional monomer. Templates extracted from polymer followed by evaluation of adsorption ability test, a test of capacity and selectivity of the polymer, and also the characterization of the IP using Fourier Transform Infra-Red (FTIR),and Scanning Electron Microscope (SEM). The results showed that IP diazepam with MAA monomer has 7.95 x 10-5 mg/g of capacity, it is better than capacity of IP diazepam monomer HEMA with 7.47x 10-6 mg/g. Selectivity of IP diazepam MAA monomer has an IF value which is 2.13, which is better than IP HEMA with 1.21. In addition, IP diazepam MAA monomer more heterogenous than its Non Imprinted Polymer (NIP).Keywords: Chloroform, Diazepam, HEMA, Methacrylic acid, MI-SPE.